Synthesis and antiviral evaluation of novel peptidomimetics as norovirus protease inhibitors. Issue 12 (1st July 2018) - Amblard, Franck; Zhou, Shaoman; Liu, Peng; Yoon, Jack; Cox, Bryan; Muzzarelli, Kendall; Kuiper, Benjamin D.; Kovari, Ladislau C.; Schinazi, Raymond F.
Graphical abstract: Abstract: A series of tripeptidyl transition state inhibitors with new P1 and warhead moieties were synthesized and evaluated in a GI-1 norovirus replicon system and against GII-4 and GI-1 norovirus proteases. Compound 19, containing a 6-membered ring at the P1 position and a reactive aldehyde warhead exhibited sub-micromolar replicon inhibition. Retaining the same peptidyl scaffold, several reactive warheads were tested for protease inhibition and norovirus replicon inhibition. Of the six that were synthesized and tested, compounds 42, 43, and 45 potently inhibited the protease in biochemical assay and GI-1 norovirus replicon in the nanomolar range.